Dose–response relationship between methadone dose and adherence to antiretroviral therapy among HIV‐positive people who use illicit opioids. (August 2015) - Lappalainen, Leslie; Nolan, Seonaid; Dobrer, Sabina; Puscas, Cathy; Montaner, Julio; Ahamad, Keith; Dong, Huiru; Kerr, Thomas; Wood, Evan; Milloy, M.‐J.
Abstract Background and Aims For HIV‐positive individuals who use illicit opioids, engagement in methadone maintenance therapy (MMT) can contribute to improved HIV treatment outcomes. However, to our knowledge, the role of methadone dosing in adherence to antiretroviral therapy (ART) has not yet been investigated. We sought to examine the relationship between methadone dose and ART adherence among a cohort of people who use illicit opioids. Design and Setting We used data from the AIDS Care Cohort to Evaluate Access to Survival Services (ACCESS) study, an ongoing prospective observational cohort of HIV‐positive people who use illicit drugs in Vancouver, Canada, linked confidentially to comprehensive HIV treatment data in a setting of universal no‐cost medical care, including medications. We evaluated the longitudinal relationship between methadone dose and the likelihood of ≥ 95% adherence to ART among ART‐exposed participants during periods of engagement in MMT. Participants Two hundred and ninety‐seven ART‐exposed individuals on MMT were recruited between December 2005 and May 2013 and followed for a median of 42.1 months. Measurements We measured methadone dose at ≥ 100 versus < 100 mg/day and the likelihood of ≥ 95% adherence to ART. Findings In adjusted generalized estimating equation (GEE) analyses, MMT dose ≥ 100 mg/day was associated independently with optimal adherence to ART [adjusted odds ratio (AOR) = 1.38; 95% confidence interval (CI) = 1.08–1.77). In a subanalysis, we observed a dose–response relationship between increasing MMT dose and ART adherence (AOR = 1.06 per 20 mg/day increase, 95% CI = 1.00–1.12). Conclusion Among HIV‐positive individuals in methadone maintenance therapy, those receiving higher doses of methadone (≥ 100 mg/day) are more likely to achieve ≥ 95% adherence to antiretroviral therapy than those receiving lower doses.